2019
DOI: 10.1212/wnl.0000000000007602
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of neuromuscular ultrasound in focal neuropathies

Abstract: ObjectiveTo evaluate the cost-effectiveness of neuromuscular ultrasound (NMUS) for the evaluation of focal neuropathies.MethodsA prior prospective, randomized, double-blind controlled trial demonstrated that NMUS, when added to electrodiagnostic testing, resulted in improved clinical outcomes after 6 months of follow-up. From this study, we abstracted quality-adjusted life-years (QALYs) from the 36-item Short Form Health Survey and entered this health-utility estimate into a mixed trial and model-based cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Recent developments in technology have begun to reduce the financial strain associated with US unit purchase, with more economical laptop-based units and US integrated into EMG machines providing adequate resolution for the evaluation of nerves in most regions of interest. Once equipped, NMUS in mononeuropathy cohorts is reported to improve quality of life outcomes, with only modest outlays on cost-effectiveness analyses[ 267 , 268 ]. While these initial studies suggest a positive benefit-outlay ratio, the overall cost-effectiveness of NMUS for diagnostics, monitoring and prognostication in neuromuscular diseases is not yet known.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Recent developments in technology have begun to reduce the financial strain associated with US unit purchase, with more economical laptop-based units and US integrated into EMG machines providing adequate resolution for the evaluation of nerves in most regions of interest. Once equipped, NMUS in mononeuropathy cohorts is reported to improve quality of life outcomes, with only modest outlays on cost-effectiveness analyses[ 267 , 268 ]. While these initial studies suggest a positive benefit-outlay ratio, the overall cost-effectiveness of NMUS for diagnostics, monitoring and prognostication in neuromuscular diseases is not yet known.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Apart from its increased diagnostic yield, the improved cost‐effectiveness of neuromuscular ultrasound cannot be ignored, especially when it concerns a large group of patients such as those with entrapment mononeuropathies 9 . One recent study showed that the addition of ultrasound in focal neuropathies is efficient from a American societal perspective, with a cost of $463 for each quality‐adjusted life‐year gained 10 . When it comes to treatment of mononeuropathies, ultrasound guidance of corticosteroid injections adds value as well 11 …”
mentioning
confidence: 99%
“…No such evidence currently exists. Furthermore, it should be noted that not only is diagnostic neuromuscular ultrasound painless, but it cost‐effectively improves outcomes 14,18 …”
mentioning
confidence: 99%
“…Furthermore, it should be noted that not only is diagnostic neuromuscular ultrasound painless, but it costeffectively improves outcomes. 14,18 What then, is the role of EDX tests, other than median nerve conduction studies, in CTS? In patients with diabetes or findings suggestive of polyneuropathy, experience suggests that additional distal nerve conduction studies may help grade electrophysiologic severity of polyneuropathy and the interpretation of median motor and sensory studies.…”
mentioning
confidence: 99%